2014
DOI: 10.1186/s13023-014-0190-9
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the phenotype of PRPS1 syndromes in females: neuropathy, hearing loss and retinopathy

Abstract: BackgroundPhosphoribosyl pyrophosphate synthetase (PRS) I deficiency is a rare medical condition caused by missense mutations in PRPS1 that lead to three different phenotypes: Arts Syndrome (MIM 301835), X-linked Charcot-Marie-Tooth (CMTX5, MIM 311070) or X-linked non-syndromic sensorineural deafness (DFN2, MIM 304500). All three are X-linked recessively inherited and males affected display variable degree of central and peripheral neuropathy. We applied whole exome sequencing to a three-generation family with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
52
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 36 publications
(62 citation statements)
references
References 29 publications
9
52
1
Order By: Relevance
“…Variants in PRPS1 encoding the protein PRS‐I cause rare forms of DFNX1, CMTX5, Arts syndrome, and PRS‐I superactivity (MIM# 300661) in affected males (Gandia et al., ; Mittal, et al., ). However, recently a family with only affected females with optic atrophy, RP and neurological features overlapping CMTX5, and Arts syndrome was reported with a PRPS1 variant affecting the same codon as we report in family 1, c.46T > C, p.(Ser16Pro) (Almoguera et al., ), implicating the PRPS1 variant as the top candidate in family 1. Sanger sequencing confirmed the PRPS1 variant in the affected female proband, and its absence in unaffected siblings (1‐II:3 and 1‐II:5, Figure and Supp.…”
Section: Resultssupporting
confidence: 60%
“…Variants in PRPS1 encoding the protein PRS‐I cause rare forms of DFNX1, CMTX5, Arts syndrome, and PRS‐I superactivity (MIM# 300661) in affected males (Gandia et al., ; Mittal, et al., ). However, recently a family with only affected females with optic atrophy, RP and neurological features overlapping CMTX5, and Arts syndrome was reported with a PRPS1 variant affecting the same codon as we report in family 1, c.46T > C, p.(Ser16Pro) (Almoguera et al., ), implicating the PRPS1 variant as the top candidate in family 1. Sanger sequencing confirmed the PRPS1 variant in the affected female proband, and its absence in unaffected siblings (1‐II:3 and 1‐II:5, Figure and Supp.…”
Section: Resultssupporting
confidence: 60%
“…SH178–411 with moderate SNHL showed a lower PRS1 activity than SH178–396 with severe SNHL. A subtle discrepancy between the degree of SNHL and residual PRS1 activities in our affected siblings is not unprecedented . A previous study also reported similar results for intrafamilial phenotypic heterogeneities .…”
Section: Discussionsupporting
confidence: 63%
“…On the other hand, destabilization of the ATP‐binding site results in PRPS1 deficiency‐related disorders, encompassing the most severe forms of PRPS1 ‐deficiency syndrome, Arts syndrome, an intermediate form between CMTX5 and Arts syndrome, and CMTX5, in accordance with the residual PRS1 activities. DFNX1 mutations usually neither influence the allosteric site, nor the ATP‐binding site but, instead, induce the local protein structural changes or effect the interface of trimers . However, the structural loci of PRPS1 mutations is not always the determining factor of the types of PRPS1 ‐deficiency disorders.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations